Symptoms of aggression on animal bones from archaeological sites - Bartosiewicz, László; Gál, Erika (Animal welfare, Ethology and Housing Systems (AWETH), 2008)
Archaeozoology is the identification, analysis and scientific as well as cultural interpretation of animal remains recovered from archaeological sites. It is the culture historical study of animal-human relationships. Owing to the extremely fragmentary nature of its data, archaeozoology is a multidisciplinary subject, heavily dependent on the integration of research results from related research.Archaeozoological finds can be used in studying human or animal beaviour only to a limited extent. However, a few traumatic lesions identified on excavated animal bones may be tentatively attributed to ancient practices of animal husbandry of direct interest to archaeologists. Such symptoms, however, may not only be indicative of simple maltreatment but often result from aggression. Therefore, it should be important to recognize damage to bone caused by conflict. In addition to intraspecific aggression in a classical sense, interspecific aggression should also be considered. This latter also includes human/cultural action. While injuries inflicted by humans are most relevant to standard archaeological inquiry, the possibly safest identification of trauma caused by natural agents (e. g. during mating fights) is a prerequisite to the recognition of patterning caused by humans. This article is a review of archaeozoological examples, aimed at the tentative discussion of ethological interpretations of observations made on archaeozoological finds.
Keywords: archaeozoology; aggression; palaeopathology; traumatic bone injury